Border medical tourism: the Ciudad Juárez medical product - Martínez Almanza, María Teresa (2018)
The pursuit of cross-border health care between the United States and Mexico has been a common practice for decades. Patients in the United States are motivated to seek medical attention in Ciudad Juárez, Mexico, due to several factors: affordability of treatment abroad, access to treatments not available at home, considerable cost differentiation, as well as long waiting lists to receive medical attention at home, among others. The results of 28 interviews with the main stakeholders are presented in this article, with the purpose of achieving a better understanding of border medical tourism. The results show a medical tourism product differentiated by various health care needs and the income of patients.